Insights into the Molecular Mechanisms and Novel Therapeutic Strategies of Stenosis Fibrosis in Crohn’s Disease - Yuan Zhou; Huiping Chen; Qinbo Wang; Guozeng Ye; Yingjuan Ou; Lihong Huang; Xia Wu; Jiaxi Fei (Biomedicines)
Crohn’s disease (CD), characterized by chronic gastrointestinal inflammation, is complicated by intestinal stenosis resulting from dysregulated fibrogenesis and is marked by excessive extracellular matrix (ECM) deposition, fibroblast activation, and luminal obstruction. While biologics control inflammation, their failure to halt fibrosis underscores a critical therapeutic void. Emerging evidence highlights the multifactorial nature of stenosis-associated fibrosis, driven by profibrotic mediators and dysregulated crosstalk among immune, epithelial, and mesenchymal cells. Key pathways, including transforming growth factor (TGF-β), drosophila mothers against decapentaplegic protein (Smad) signaling, Wnt/β-catenin activation, epithelial–mesenchymal transition (EMT), and matrix metalloproteinase (MMP) and tissue inhibitors of metalloproteinase (TIMP)-mediated ECM remodeling, orchestrate fibrotic progression. Despite the current pharmacological, endoscopic, and surgical interventions for fibrostenotic CD, their palliative nature and inability to reverse fibrosis highlight an unmet need for disease-modifying therapies. This review synthesizes mechanistic insights, critiques therapeutic limitations with original perspectives, and proposes a translational roadmap prioritizing biomarker-driven stratification, combinatorial biologics, and mechanistically targeted antifibrotics.